Induction of Ferroptosis by Ophiopogonin-B Through Regulating the Gene Signature AURKA in NSCLC - Li, Liqiu; Gao, Qian; Wang, Jin; Gu, Ling; Li, Zhihui; Zhang, Shiping; Hu, Cheng; He, Menglin; Wang, Yulin; Wang, Zixuan; Yi, Yongxiang; Fu, Jin; et al. (Frontiers in Oncology, 2022)
Ferroptosis is a new type of iron-dependent programmed cell death. In recent years, its role in the diagnosis and treatment of multiple tumors, including non-small cell lung cancer (NSCLC), has been continuously observed. The relationship between the ferroptosis-related genes and the prognosis of patients with NSCLC needs to be clarified. In this study, The Cancer Genome Atlas (TCGA) and the Gene Expression Synthesis database (Gene Expression Omnibus, GEO) were used to build a model of ferroptosis-related differentially expressed genes (DEGs). A total of 101 ferroptosis-related DEGs were screened using R language, and a 12-gene signature was finally established through univariate Cox regression analysis and least absolute shrinkage and selection operator (LASSO)-penalized Cox regression analysis. According to the risk scores, the patients were divided into a high-risk or a low-risk group, with patients in the low-risk group showing better prognosis. AURKA, one of the genes in the 12-gene signature, was found to be highly expressed in tumors. In addition, further study verified AURKA to be a negative regulator of ferroptosis in NSCLC cells. Ophiopogonin B (OP-B) had been reported to induce apoptosis, mitotic catastrophe, and autophagy in NSCLC cells. Herein, proteomic sequencing analysis and OP-B administration revealed the upregulation of AURKA and the downregulation of PHKG2 and SLC7A5 in the 12-gene signature, indicating that OP-B induced ferroptosis in NSCLC. Determination of the concentrations of malondialdehyde (MDA), glutathione (GSH), and intracellular iron and the mitochondrial membrane potential (MMP) confirmed the induction of ferroptosis by OP-B in vitro. Furthermore, transmission electron microscopy (TEM) examination of lung cancer xenotransplantation in nude mice confirmed that OP-B induced ferroptosis in vivo. Further study of the molecular mechanism showed that the ferroptosis effect caused by OP-B can be partially reversed by the overexpression of AURKA. Overall, our study established a new ferroptosis-related risk prediction model for the prognosis of patients with NSCLC, revealed the enrichment pathways of ferroptosis in NSCLC, and discovered the negative regulation of AURKA in ferroptosis. On this basis, we demonstrated that OP-B can induce ferroptosis in NSCLC and clarified the specific molecular mechanism of OP-B inducing ferroptosis by regulating the expression of AURKA.